دور الإدارة المدرسية في توطيد العلاقة بين المدرسة والمجتمع المحلي في المدارس الثانوية العامة من وجهة نظر المدرسين في حمص - ذياب رشا (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The research has aimed to identify the role of school management in maintaining the relationship between the school and the local community in Homs and knowing the different responses of teachers participating in the research depending on the two criteria of (sex , years of teaching experience) . The sample consisted of (303) male and female teachers who have been chosen randomly from the schools of Homs city. The researcher has followed the Descriptive approach in her survey and she has used a questionnaire kind of survey as a means to achieve the objectives of the research after it was tested for its validity and reliability. The most important findings of the study: 1 –The role of school management in maintaining the relationship between the school and the local community has been highly evaluated by the teachers of the public secondary schools in Homs. 2 - There were no statistical significant differences in the average rate of teachers’ responses on the role of school management in maintaining the relationship between the school and the local community according to the variable of sex. 3– There were statistical significant differences in the average rate of teachers’ responses on the role of school management in maintaining the relationship between the school and the local community according to the variable of years of teaching experience for teachers with high record of years of experience. هدف هذا البحث إلى التعرف إلى دور الإدارة المدرسية في توطيد العلاقة بين المدرسة والمجتمع المحلي في المدارس الثانوية العامة من وجهة نظر المدرسين في حمص ومعرفة الفروق في إجابات المدرسين على أداة البحث تبعاً لمتغيري (الجنس، وسنوات الخبرة التدريسية). وتكونت عينة البحث من (303) مدّرساً ومدّرسة، تم اختيارهم بالطريقة العشوائية من مدارس حمص، وقد اتبعت الباحثة المنهج الوصفي في البحث واستخدمت الاستبانة كأداة لتحقيق أهداف البحث بعد التحقق من صدقها وثباتها. ومن أهم النتائج التي توصلت إليها الدراسة: 1- وجود تقييم مرتفع لدور الإدارة المدرسية في توطيد العلاقة بين المدرسة والمجتمع المحلي لدى مدرسي المدارس الثانوية العامة في حمص. 2- عدم وجود فروق ذات دلالة إحصائية في متوسط درجات المدرسين على استبانة دور الإدارة المدرسية في توطيد العلاقة بين المدرسة والمجتمع المحلي وفقاً لمتغير الجنس. 3- وجود فروق ذات دلالة إحصائية في متوسط درجات المدرسين على استبانة دور الإدارة المدرسية في توطيد العلاقة بين المدرسة والمجتمع المحلي وفقاً لمتغير سنوات الخبرة التدريسية لصالح المدرسين ذوي سنوات الخبرة الأعلى.